2012
DOI: 10.1016/j.physio.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Intertester reliability of a classification system for shoulder pain

Abstract: This clearly defined system uses key elements of the history and examination to classify patients with shoulder pain. The kappa coefficient denotes good reproducibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Poor reliability findings have been reported for tests used in physical examinations in general, with similar results in many other areas of the body [24]. In light of the poor reliability of shoulder examination tests, it has been suggested that expert clinicians consider their results within the context of the patient interview and patterns of physical examination findings, rather than relying on one key finding or outcome measure [24, 28, 29]. Considering the difficult nature of physical examinations of the shoulder and the limited reliability seen in face-to-face studies, the strong agreement found in this study between face-to-face and telerehabilitation assessment is convincing evidence for the validity of online physical assessments of the shoulder.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor reliability findings have been reported for tests used in physical examinations in general, with similar results in many other areas of the body [24]. In light of the poor reliability of shoulder examination tests, it has been suggested that expert clinicians consider their results within the context of the patient interview and patterns of physical examination findings, rather than relying on one key finding or outcome measure [24, 28, 29]. Considering the difficult nature of physical examinations of the shoulder and the limited reliability seen in face-to-face studies, the strong agreement found in this study between face-to-face and telerehabilitation assessment is convincing evidence for the validity of online physical assessments of the shoulder.…”
Section: Resultsmentioning
confidence: 99%
“…Stronger agreements were achieved for inter-rater reliability (73.1%) and intra-rater reliability (100%) combining same and similar agreements. Previous research on the reliability of face-to-face examinations of the shoulder reveals conflicting results [21, 2931]. Some studies reported very good agreements (Pellecchia et al [31], 90.5% agreement, κ = 0.875; Carter et al [29], 80% agreement, κ = 0.664), whereas others report poorer agreement rates (De Winter et al [30]; 60% agreement, κ = 0.45, Bamji et al [21]; 46% agreement, no kappa recorded).…”
Section: Resultsmentioning
confidence: 99%
“…We do have diagnostic methods like arthroscopy and MRI for diagnosis of shoulder disorders but either they are invasive or costly. One of the clinical characteristic through which shoulder problem can successfully be diagnosed isPain [8] . The intensity, location, type and duration of pain might help to diagnose the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Use of pain map for specific disorder has been described for back and hip pain. In recent years, some attempts have been made to come up with some systematic methodology to understand these patterns in order to understand the etiology, chronicity and severity of shoulder pain [8,9] . No study has specifically reported distribution and type of pain in common shoulder disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, objectively identifying maximal ROM during active motion, often requires direct intervention by the clinician, interrupting natural motion to take "snapshot" measurements or requiring the patient to conform to prescribed artificial motion constraints that might not always reflect normal movement. Despite attempts to standardise ROM measures [21][22][23][24], to date there is not a simple satisfactory method for evaluating active rotational ROM of the shoulder in real time. Not only does this pose a problem for supervising clinicians, but also for the patient attempting to carry out unsupervised exercises, with no meaningful way to evaluate correct performance or improvements in mobility.…”
Section: Introductionmentioning
confidence: 99%